A Survey of Automatic Protocol Reverse Engineering Approaches, Methods, and Tools on the Inputs and Outputs View. (20th February 2018) - Sija, Baraka D.; Goo, Young-Hoon; Shim, Kyu-Seok; Hasanova, Huru; Kim, Myung-Sup
Abstract : A network protocol defines rules that control communications between two or more machines on the Internet, whereas Automatic Protocol Reverse Engineering (APRE) defines the way of extracting the structure of a network protocol without accessing its specifications. Enough knowledge on undocumented protocols is essential for security purposes, network policy implementation, and management of network resources. This paper reviews and analyzes a total of 39 approaches, methods, and tools towards Protocol Reverse Engineering (PRE) and classifies them into four divisions, approaches that reverse engineer protocol finite state machines, protocol formats, and both protocol finite state machines and protocol formats to approaches that focus directly on neither reverse engineering protocol formats nor protocol finite state machines. The efficiency of all approaches' outputs based on their selected inputs is analyzed in general along with appropriate reverse engineering inputs format. Additionally, we present discussion and extended classification in terms of automated to manual approaches, known and novel categories of reverse engineered protocols, and a literature of reverse engineered protocols in relation to the seven layers' OSI (Open Systems Interconnection) model.